2015
DOI: 10.1002/arch.21251
|View full text |Cite
|
Sign up to set email alerts
|

CHARACTERIZATION AND FUNCTIONAL STUDY OF A PUTATIVE JUVENILE HORMONE DIOL KINASE IN THE COLORADO POTATO BEETLE Leptinotarsa decemlineata (Say)

Abstract: Juvenile hormone diol kinase (JHDK) is an enzyme involved in JH degradation. In the present article, a putative JHDK cDNA (LdJHDK) was cloned from the Colorado potato beetle Leptinotarsa decemlineata. The cDNA consists of 814 bp, containing a 555 bp open reading frame encoding a 184 amino acid protein. LdJHDK reveals a high degree of identity to the previously reported insect JHDKs. It possesses three conserved purine nucleotide-binding elements, and contains three EF-hand motifs (helix-loop-helix structural d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 55 publications
3
14
0
Order By: Relevance
“…There were 3 conserved sequence elements responsible for purine nucleotide binding and 3 elongation factor (EF)-hand motifs in both dSCP2 and GTP-binding proteins (Maxwell et al 2002a,b). Several JHDK cDNAs have been identified from insect species, such as Danaus plexippus L. (Lepidoptera: Nymphalidae), Plutella xylostella L. (Lepidoptera: Plutellidae), and B. mori (Li et al 2005), Ostrinia furnacalis Guenée (Lepidoptera: Crambidae) (Feng & Zhai 2011), Spodoptera litura F. (Lepidoptera: Noctuidae) (Zeng et al 2015), and L. decemlineata (Fu et al 2015). The recombinant Bm-JHDK of B. mori in Sf9 cells using a baculovirus system converted 10S-JH diol to form JHdp, suggesting its enzymatic function in JH regulation (Li et al 2005).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…There were 3 conserved sequence elements responsible for purine nucleotide binding and 3 elongation factor (EF)-hand motifs in both dSCP2 and GTP-binding proteins (Maxwell et al 2002a,b). Several JHDK cDNAs have been identified from insect species, such as Danaus plexippus L. (Lepidoptera: Nymphalidae), Plutella xylostella L. (Lepidoptera: Plutellidae), and B. mori (Li et al 2005), Ostrinia furnacalis Guenée (Lepidoptera: Crambidae) (Feng & Zhai 2011), Spodoptera litura F. (Lepidoptera: Noctuidae) (Zeng et al 2015), and L. decemlineata (Fu et al 2015). The recombinant Bm-JHDK of B. mori in Sf9 cells using a baculovirus system converted 10S-JH diol to form JHdp, suggesting its enzymatic function in JH regulation (Li et al 2005).…”
mentioning
confidence: 99%
“…The recombinant Bm-JHDK of B. mori in Sf9 cells using a baculovirus system converted 10S-JH diol to form JHdp, suggesting its enzymatic function in JH regulation (Li et al 2005). In L. decemlineata, knockdown of LdJHDK significantly increased the hemolymph JH titer and negatively affected adult emergence (Fu et al 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At the wandering stage, JH titer obviously decreased [41], and the expression of JH degradation genes were activated [39]. Here we found that ingestion of JH (Fig 2F), or knockdown of an allatostatin gene ( AS-C ) [41] or either of two JH degradation genes (JH epoxide hydrolase, JHEH1 ; JH diol kinase, JHDK ) [35, 39] to delay JH decrease significantly reduced light avoidance (Fig 2G and S1E-G Fig) and postponed the occurrence of wandering (S2 Table); whereas knockdown of a JH biosynthesis gene (JH acid methyl transferase, JHAMT ) [34] and a JH receptor gene (methoprene-tolerant, Met ) to prematurely reduce JH signal enhanced light avoidance (Fig 2H and S1H, I Fig) and accelerated the onset of wandering (S2 Table). It is clear that JH signal inhibits the premature switch of light preference and the early onset of wandering.…”
Section: Resultsmentioning
confidence: 91%
“…This makes CPB an excellent candidate for pest management using dsRNAs, which was first recognized in a study by Baum et al (2007) that has also identified several RNAi targets. This was followed by studies that identified novel effective target genes in CPB (Zhu et al 2011Zhou et al 2013;Wan et al 2014;Meng et al 2015Meng et al , 2018Lü et al 2015;Fu et al 2015Fu et al , 2016Shi et al 2016b, a;Guo et al 2016;Xu et al 2018). In western corn rootworm, Hu et al (2016) identified another target gene -mesh (alternatively named dvssj2) which encodes a smooth septate junction protein important for structural integrity of the midgut epithelium.…”
Section: Introductionmentioning
confidence: 99%